Pelatihan Instalasi Penerangan Untuk Mahasiswa Teknik Elektro - Novi Kurniasih (Sekolah Tinggi Teknik - PLN, 2020)
The training of lighting installations for electrical engineering students is intended to provide an understanding of the electricity dangers and skills in terms of installing lighting installations that comply with PUIL standards. With the training of this lighting installation, it can help electrical engineering students to install and repair electrical installations independently even with having these skills can make those students open business opportunities so that employment opportunities will be open and at least they will have income for themselves. This training is given in two stages, namely the stage of supply material and the material testing phase, both theoretically and practically. With this training, the trainees are expected to understand well about the electricity dangers and how to secure it, read installation drawings, measure voltage, detect broken connections, and can make lighting installations using various switches and sockets that comply with the standards and conditions in PUIL and SPLN. In designing and installing electrical installations systems must be considered about human safety, other living things and the security of property from harm and damage that can be caused by the use of electrical installations. Through the Community Partnership Program, electrical engineering lecturer team of IT–PLN felt to need to conduct community training which is currently only focused on electrical engineering students of Pertamina University, by providing knowledge about lighting installation engineering skills. By utilizing experts in the electrical engineering department of IT–PLN, it is expected to be able to add skills and knowledge to electrical engineering students of Pertamina University. The trainees are expected to have an understanding of the electricity theory, the dangers of electricity and how to deal with it and have a strong desire to obtain theoretical and practical knowledge about electrical lighting installation techniques.